Case Report: A rare case of external iliac artery rupture and sigmoid fistula following multimodal treatment for cervical cancer - Cheng, Xu; Wang, Jiantao; Wang, Huanzhong; Song, Haotian; Zhao, Guoping; Wang, Hongzhi (Frontiers in Oncology, 2026)
We report a 58-year-old woman with cervical squamous cell carcinoma who developed an early-onset left external iliac artery rupture followed by a sigmoid fistula after multimodal treatment. Notably, key baseline tumor parameters-including maximal tumor diameter and stromal invasion depth-were not documented preoperatively because PET-CT was not performed and the original MRI/CT datasets from the outside hospital were unavailable. This incomplete staging likely contributed to underestimation of disease extent and to selection of a non-guideline-concordant primary radical hysterectomy, although postoperative pathology ultimately confirmed FIGO 2018 stage IIIC2 disease with extensive nodal metastases. The patient subsequently received adjuvant pelvic external-beam radiotherapy and vaginal cuff high-dose-rate brachytherapy. One month after completing radiotherapy, she presented with acute hematochezia and hemorrhagic shock. Angiography revealed active extravasation from the left external iliac artery adjacent to a postoperative lymphocele, and a covered stent was deployed with temporary hemostasis. Despite intensive antimicrobial and supportive therapy, she later developed a sigmoid fistula, pelvic abscess, recurrent bleeding, and persistent sepsis, culminating in fatal deterioration. The arterial rupture was considered to be multifactorial, with potential contributions from extensive lymphadenectomy, lymphocele formation, infection, and radiation-related tissue fragility. This case underscores the critical importance of comprehensive preoperative assessment and guideline-based primary treatment selection in cervical cancer, as inappropriate initial management may predispose patients to severe lymphatic, infectious, and vascular complications. Early multidisciplinary surveillance and timely intervention may be essential to prevent catastrophic outcomes. In gynecologic oncology, the combination of early-onset iliac arterial rupture and subsequent sigmoid fistula shortly after postoperative radiotherapy remains exceedingly rare, and to our knowledge has not been previously reported in a patient with unrecognized FIGO IIIC2 disease at initial treatment.